2016
DOI: 10.6007/ijarems/v5-i2/2211
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Debt on Economic Growth of Pakistan

Abstract: This study is an attempt to explore the impact of public debt on economic growth of Pakistan. To explore the relationship the study used augmented Solow growth Model. To test the model, Bound test for Cointegration is applied on time series data that cover the period from 1972 to 2013. The empirical results of the study suggest that public debt and economic growth has positive but statistically insignificant relationship. In addition, our control variables i.e., population growth enter in the model with expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Particularly, it agrees with studies made by Were (2001), Presbitero (2006), Sen et al (2007), Adegbite et al (2008), Hwang et al (2010), Malik et al (2010), Daud and Podivinsky (2012), Azam et al (2013), Atique and Malik (2012), Shabbir (2013), Lee and Ng (2015), Daka et al (2017), Pegkas (2018), Shittu et al (2018), Shkolnyk and Koilo (2018), Kharusi and Ada (2018), Sajjad et al (2018), Senadza et al (2018), Nor-Eddine andChkiriba (2019), and Moh and Jaradat (2019) who found that debt overhang dilemma prevails. However, these findings are contradictory to the findings of Siddiqui and Malik (2001), Maana et al (2008), Khan et al (2016), Jilenga et al (2016), Sánchez-Juárez and García-Almada (2016, Talreja et al (2016), Chaudhry et al (2017), andNdubuisi (2017), who found that debt overhang dilemma does not prevails. For them, overseas borrowing acts as a stimulating factor for the economic growth.…”
Section: Long Run Estimatesmentioning
confidence: 74%
See 2 more Smart Citations
“…Particularly, it agrees with studies made by Were (2001), Presbitero (2006), Sen et al (2007), Adegbite et al (2008), Hwang et al (2010), Malik et al (2010), Daud and Podivinsky (2012), Azam et al (2013), Atique and Malik (2012), Shabbir (2013), Lee and Ng (2015), Daka et al (2017), Pegkas (2018), Shittu et al (2018), Shkolnyk and Koilo (2018), Kharusi and Ada (2018), Sajjad et al (2018), Senadza et al (2018), Nor-Eddine andChkiriba (2019), and Moh and Jaradat (2019) who found that debt overhang dilemma prevails. However, these findings are contradictory to the findings of Siddiqui and Malik (2001), Maana et al (2008), Khan et al (2016), Jilenga et al (2016), Sánchez-Juárez and García-Almada (2016, Talreja et al (2016), Chaudhry et al (2017), andNdubuisi (2017), who found that debt overhang dilemma does not prevails. For them, overseas borrowing acts as a stimulating factor for the economic growth.…”
Section: Long Run Estimatesmentioning
confidence: 74%
“…Shahzad et al (2014) also concluded that external debt dampens the growth process in Pakistan. In contrast, Khan et al (2016) found that the association of public debt with the economic growth is positive but statistically insignificant. On the other hand, the findings of Jibran et al (2016) and Sajjad et al (2018) indicated that debt crowding-out hypothesis is effective for Pakistan's economy.…”
Section: Literature On the External Debt And Growth Relationship In Pakistanmentioning
confidence: 81%
See 1 more Smart Citation
“…External debt and economic growth relationships are exposed [38] and concluded that external debt has a positive and significant impact on economic growth. The influence of public debt on economic growth analysed [39], and based on empirical outcomes, researchers revealed a positive but insignificant relationship between public debt and the economic growth of Pakistan. The connection between central government debt, external debt, household debt, and GDP was analysed [40].…”
Section: Research Elaborationsmentioning
confidence: 99%
“…The study also discovered that budget deficit, government consumption and external debt service are a decreasing function of GDP. Khan, Rauf, Mirajul-haq, Anwar (2016) examined the impact of public debt on economic growth of Pakistan. The study adopted quantitative research method as secondary data over the period of 1972 to 2013.…”
Section: Empirical Evidencesmentioning
confidence: 99%